Numerical analysis of a photovoltaic panel containing hybrid nanoparticles integrated with PCM in the presence of fixed fins - Ali Gholami; Kosar Parach; Bahram Jafari (Case Studies in Thermal Engineering)
Using phase change materials (PCMs) with nanomaterials to enhance and regulate the temperature of photovoltaic (PV) panels has been effective. In this study, Na2SO4·10H2O was mixed with Al2O3 and MgO nanoparticles at weight concentrations of 3 % and 7 %, and the performance of the PV/HPCM system was numerically analyzed. The model incorporates copper fins and aluminum heat sinks. The temperature and liquid fraction distributions in the PCM chamber show that phase change starts near the copper fins and progresses toward the aluminum heat sinks. This indicates that PCMs near the copper fins reach the phase change threshold temperature faster and begin melting more quickly, while those near the heat sinks undergo a slower heat transfer process due to aluminum's lower heat transfer coefficient. Increasing the concentration of hybrid nanoparticles MgO and Al2O3 boosts heat transfer, thereby improving PV panel efficiency. The maximum efficiency of the PV panel for the PV/PCM system is 21.15 %, while for the PV/HPCM system, it reaches 22.62 % with a 3 % weight concentration of nanomaterials and 24 % with a 7 % concentration. The efficiency difference between the PV/PCM and PV/HPCM systems at a 3 % weight concentration is 4 %, increasing to 6.2 % at a 7 % concentration.